Resin content calculation of carbon fiber/poly (ether ether ketone) by thermogravimetric analysis. (January 2023) - Lu, Chunrui; Ma, Wenlong; Ba, Shuhong; Zhang, Dongxing
Abstract: Resin content of composites is a dominant factor of macroscopic properties and essential to study. Taking carbon fiber/poly (ether ether ketone) (CF/PEEK) composites molded by various means as examples, a method for resin content calculation obtained along with thermogravimetric analysis (TGA) for thermal properties analyzation was introduced. According to results of resin mass contents, TGA curves and differential thermogravimetric analysis (DTG) curves were divided to four stages, including non-decomposition stage of 25–500 °C, rapid decomposition stage of 500–600 °C, transitional stage of 600–700 °C and the stable stage of 700–800 °C. And resin contents were accurate obtained from the transitional stage and stable stage. Results tested by acid digestion method, ignition loss method and TGA methods were compared and it was proved that the TGA method was suitable for resin fraction calculation with a slight difference below 3% compared to results from the other two methods. By comparing results of different composites, we found that TGA methods can also be applied to other composites including reinforcements not disintegrate such as graphite, carbon nanotubes and matrix of thermosetting and thermoplastic decompose under inert gas in testing condition. Highlights: TGA curves including PEEK matrix and CF/PEEK composites can be applied for resin content calculation. The slow decomposition stage and stable stage of TGA curves (600 °C-800 °C) are suitable for resin content study. TGA method is available and accurate based on the uniformity of composites composed of decomposable polymers and non-decomposable or little-decomposable reinforcements under inert atmosphere in the testing scope.